The Potential of Neurofeedback in the Treatment of Eating Disorders: A Review of the Literature. (30th September 2013) - Bartholdy, Savani; Musiat, Peter; Campbell, Iain C.; Schmidt, Ulrike
Abstract: Neurofeedback is defined as the training of voluntary regulation of localised neural activity using real‐time feedback through a brain‐computer interface. It has shown initial success as a potential clinical treatment tool in proof of concept studies, but has yet to be evaluated with respect to eating disorders. This paper (i) provides a brief overview of the current status of eating disorder treatments; (ii) describes the studies to date that use neurofeedback involving electroencephalography, real‐time functional magnetic resonance imaging or near‐infrared spectroscopy; and (iii) considers the potential of these technologies as treatments for eating disorders. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.